An Efficient Method to Separate Sc3N@C80Ih and D5h Isomers and Sc3N@C78 by Selective Oxidation with Acetylferrocenium [Fe(COCH3C5H4)Cp]+. Issue 23 (10th April 2013) - Cerón, Maira R.; Li, Fang‐Fang; Echegoyen, Luis
Abstract Based on the different oxidation potentials of endohedral fullerenes Sc3N@C80 Ih and D5h and Sc3N@C78, an efficient and useful method that avoids HPLC has been developed for their separation. Selective chemical oxidation of the Sc3N@D5h‐C80 isomer and Sc3N@C78 by using an acetylferrocenium salt [Fe(COCH3C5H4)Cp]+ followed by column chromatographic separation and reduction with CH3SNa resulted in the isolation of pure Sc3N@Ih‐C80, Sc3N@C78, and a mixture of Sc3N@D5h‐C80 and Sc3N@C68.